NMG expands NA distribution (Reinforced Plastics, 2016)
Background Healthy nursing work environments are recognized as key drivers of patient safety, workforce stability, and organizational performance, but existing evidence is fragmented and difficult to operationalize. Purpose This scoping review synthesizes recent literature (2021-2025) examining associations between nursing work environments and patient, workforce, and organizational outcomes across health care settings. Methods Following Joanna Briggs Institute and PRISMA-ScR guidance, a structured search of CINAHL Ultimate and Google Scholar identified 75 records. After screening, 25 studies and reports were included. Data were extracted and organized into patient, workforce, and organizational outcome categories, with narrative synthesis used to identify patterns and gaps. Results Across diverse settings and methods, findings consistently show that favorable work environments are associated with improved patient safety and experience, lower nurse burnout and turnover intention, higher job satisfaction, and stronger organizational performance indicators such as safety climate and quality of care. Evidence from ambulatory and emergency settings, though limited, demonstrates similar directional relationships. Measurement approaches varied, but positive associations were consistent across instruments and levels of analysis. Conclusion The nursing work environment is a modifiable, system-level lever with consistent links to improved outcomes. Strengthening work environments represents a practical, evidence-based strategy for enhancing patient care, supporting workforce well-being, and improving organizational performance.